Edukasi Keamanan Kosmetik: Mengenal Cek KLIK dan Bahaya Kosmetik Tidak Terdaftar BPOM - Leppan, Sryseptia; Auliyaurrahman, Arina; Permatasari, Selvy; Prasesti, Gayuk Kalih (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The health promotion activity titled “Cosmetic Safety Education: Understanding Cek KLIK and the Dangers of Unregistered Cosmetics” aimed to improve students’ knowledge of cosmetic safety at SMK Kesehatan Samarinda. The intervention used a lecture–discussion method supported by leaflet and PowerPoint media, accompanied by pre-test and post-test assessments. The pre-test results showed an average score of 59%, indicating limited understanding of cosmetic notification, hazardous ingredients, and the Cek KLIK steps for verifying product safety. After the educational session, the average score increased to 86%, resulting in a 28% improvement. Evaluation findings revealed that 79.7% of participants considered the activity highly beneficial, with 65.5% expressing high satisfaction. Furthermore, 62.1% rated the material delivery as very good, and 72.4% found the leaflet easy to understand. Overall, the program effectively enhanced students’ knowledge and provided significant educational benefits.